2011
DOI: 10.1007/s10552-011-9824-6
|View full text |Cite
|
Sign up to set email alerts
|

What factors do cancer patients believe contribute to the development of their cancer? (New South Wales, Australia)

Abstract: Cancer patients specified a broad range of factors and agents to which their disease may be attributed. Some of these were poorly correlated with epidemiological rankings of attributable risk factors. The role of psychosocial and genetic factors was overstated. Misconceptions regarding the causes of cancer are a key consideration of health professionals when devising communication strategies around cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 29 publications
6
38
0
Order By: Relevance
“…In addition, breast cancer patients in six studies included in the review identified oral contraceptive pills as causal [16,24,36,38,40,42], which was identified by 1.5% (n=23)…”
Section: Biological Attributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, breast cancer patients in six studies included in the review identified oral contraceptive pills as causal [16,24,36,38,40,42], which was identified by 1.5% (n=23)…”
Section: Biological Attributionsmentioning
confidence: 99%
“…The review suggests that many breast cancer survivors and patients believe that stress contributes to the development of breast cancer. Despite the lack of evidence that stress causes cancer, sixteen studies found that women attributed their breast cancer to their experience of stress [9,13,15,16,24,[35][36][37][38][40][41][42][43][50][51][52].Moreover, stress was identified as the leading cause of breast cancer in five studies [15,35,37,38,42]. In a study by Oba et al, [35] 70% (n=44) of the sample attributed their cancer to stress.…”
Section: Causal Attributions Identified But Not Validated By Expert Cmentioning
confidence: 99%
See 3 more Smart Citations